The journey of tumor-infiltrating lymphocytes as a biomarker in breast cancer: clinical utility in an era of checkpoint inhibition - Loi, S.; Michiels, S.; Adams, S.; Loibl, Sibylle; Budczies, Jan; Denkert, C.; Salgado, R. (Annals of oncology, 2021)
In 2014, we described a method to quantify percentage of tumor-infiltrating lymphocytes (TILs) on hematoxylin and eosin-stained slides of breast cancer samples using light microscopy that could be performed easily by pathologists with no extra stains. The aim of detailing the method was to facilitate independent research groups replicating our prognostic findings using TIL quantity in early-stage breast cancers. A global working group of breast pathologists was convened to standardize, test reproducibility, and refine the method. A website was also established which allowed free training (www.tilsinbreastcancer.org). As a result of this work, TIL data have been collected in over 20 000 primary breast cancer samples worldwide and the robust associations with better prognoses in triple-negative breast cancer (TNBC) and HER2+ BC have been confirmed. This has resulted in the inclusion of the TIL biomarker in several international breast cancer guidelines as well as in national criteria for routine pathology reporting. TIL therefore represents the first biological prognostic biomarker for early-stage TNBCs, and here its prognostic effect is linear, with values of 30%-50% being suggested as suitable for use in potential chemotherapy de-escalation studies. The efficacy of immune checkpoint-targeted agents in breast cancer now provides direct evidence that host immune responses can modify tumor growth in some patients. With the recent granting of accelerated approvals for the first PD-1/PD-L1 targeting agents in early and advanced TNBC, our focus has now moved to investigating the clinical utility of TIL in the setting of immune checkpoint agents, with or without PD-L1 protein assessment. Emerging data suggest that TIL quantity can help clinicians identify patients with breast cancer who benefit most from PD-1/PD-L1 inhibition. In patients with advanced TNBC and HER2+ disease a TIL cut-off of 5% or 10%, with PD-L1 expression can define ‘immune-enriched’ tumors and currently seems to have the most clinical relevance in this context.
Gesehen am 29.01.2022